Nilai-Nilai Pendidikan Karakter dalam Hadis Riwayat Imam Al-Darimi - Maisyaroh, Roosa; Muhid; Nurita , Andris (Mu'allim, 2024)
This journal aims to analyze the values of character education in the hadith narrated by Imam al-DÄrimÄ« in his Sunan book. By using hadith sharia theory which aims to understand further the context of the hadith being studied, as well as the values contained in the hadith. It is hoped that the findings of this journal will provide a deeper understanding of the hadiths narrated by Imam al-DÄrimÄ« as well as moral values that can be applied in everyday life. This aims to understand the dynamics of practice and the meaning of character education itself, so that it can provide comprehensive insight and implications in the practice of implementing it. Meanwhile, the research method in this journal uses qualitative research methods, which are sourced from the main literature, the Sunan book by Imam al-DÄrimÄ« as data collection. The results of this research include three main aspects of character education values from the hadith narrated by Imam alDÄrimÄ«. First, the biography of the author of the book, namely Imam al-DÄrimÄ«. Second, this research identifies character education from a hadith perspective narrated by Imam al-DÄrimÄ«. Third, this research reveals the hadith analysis of the values of character education in the hadith narrated by Imam al-DÄrimÄ«.